Analisis Pemanfaatan Lingkungan Sekolah sebagai Sumber Belajar Pembelajaran IPS Kelas V SDN Unyur Serang - Apriyanti, Sherly; Ridwan, Ita Rustiati; Alfarisa, Fitri (Universitas Pendidikan Indonesia Kampus Serang, 2021)
In social studies learning, the teacher had not optimized the environment around the school as a learning resource, which is expected to increase student motivation and learning outcomes. The purpose of this research were to: 1) describe the use of the school environment as a learning resource, and 2) design the use of the school environment as a learning resource in social science learning. This study used a qualitative approach with descriptive analysis method. The data in this study were the results of observations and interviews conducted at the time of the study. The research data collection technique used observations and interviews. Data were analysed using three stages, namely data reduction, data presentation and data verification. The results showed that: 1) the activities of using the school environment as a learning resource for social studies learning in class V have been frequently carried out. 2) Learning activities that take advantage of the school environment must of course be carefully prepared since this learning activity had wide and open spaces and also different challenges during teaching in the classroom. The planning of the use of the school environment as a learning resource is made in the form of a fifth grade social science lesson plan using the theme 8 Our Friends Environment. Teacher is expected to optimize the environment around the school as a learning resource in social science learning since it is potentially to increase student motivation and learning outcomes.